Hollow Co3O4 dodecahedrons with controlled crystal orientation and oxygen vacancies for the high performance oxygen evolution reaction. (29th October 2020) - Yang, Hang; Sun, Hui; Fan, Xiaochen; Wang, Xiaozhong; Yang, Qingfeng; Lai, Xiaoyong
Abstract : Hollow Co3 O4 dodecahedrons with the selective exposure of the (111) facet and controlled oxygen vacancies for high performance OER. Abstract : Rational design and preparation of advanced electrocatalysts for the oxygen evolution reaction (OER) are highly desirable, where various strategies have been applied to enhance the electrocatalytic activities, such as developing nanostructures, facet control, and creating oxygen vacancies. Herein, we have successfully integrated multiple strategies into one catalytic system for further enhancing the OER performance. A series of hollow Co3 O4 dodecahedrons with controlled crystal orientation and oxygen vacancies were prepared by using ZIF-67 as a precursor and adjusting the atmosphere during calcination. Hollow Co3 O4 dodecahedrons with both controlled exposure of the (111) facets and high content of oxygen vacancies showed an excellent OER performance with an overpotential of 307 mV at 10 mA cm −2 and a Tafel slope as low as 55 mV dec −1 and significantly superior to its counterpart with low content of oxygen vacancies or a broken Co3 O4 dodecahedron being ground and losing the preferred facets of (111). The excellent OER performance should be attributed to the unique hollow structure and the effective control of the (111) facets and oxygen vacancies, which allows for more highly active sites and enhanced conductivity.